Screw only versus screw plus plate in isolated talonavicular arthrodesis. Issue 7 (October 2022) - Goh, Tae Sik; Han, Jung Bum; Lee, Sang Min; Kang, Suk-Woong; Shin, Won Chul; Woo, Seung Hun
Abstract: Background: We aimed to compare outcomes of treatment of isolated talonavicular arthrodesis (ITNA) with screw only or screw plus plate, respectively. Methods: We retrospectively evaluated 40 consecutive cases of ITNA [two-screw fixation patients: Group 1 (23 cases); screw-plus-plate fixation patients: Group 2 (17 cases)]. Outcome measures included radiographic findings, Foot and Ankle Outcome Scores (FAOS), and visual analogue scale (VAS) scores. Results: Nonunion occurred more frequently in group 1 (21.7%) than in group 2 (5.9%), but there was no statistical significance (p = 0.216). Although the preoperative FAOS and VAS score showed similar results between both groups, there were significantly better clinical outcomes in two of five FAOS domains and VAS scores at 3 months postoperative and final follow-up (p < 0.05). Conclusion: Although union rates were not significantly different, nonunion occurred more frequently in screw only group and we obtained more favorable clinical outcomes in screw plus plate group.